Sistem Informasi Data Warehouse Penjualan Hasil Tambak Berbasis Website Pada CV. Alam Jaya - Ismasari Nawangsih (Jurnal SIGMA, 2020)
Business opportunities in the fishing industry have very promising opportunities because the food needs of the world community continue to increase from year to year. CV. Alam Jaya, which is engaged in the aquaculture industry in running its business, has not been computerized so that it often has problems in running its business such as filing company data that has not been properly organized which results in frequent redundancies, inconsistency in data and the length of the process in making purchase and sales reports. The Action Research method is used in this study as a guide in designing a website-based information system that can minimize errors that often occur, speed up work time and make it easier for company owners to manage company operational data. Keywords : Database, business, fisheries